The association between patterns of physical activity and sedentary time with frailty in relation to cardiovascular disease. Issue 1 (19th March 2019) - Kehler, Dustin Scott; Clara, Ian; Hiebert, Brett; Stammers, Andrew Nicholas; Hay, Jacqueline; Schultz, Annette; Arora, Rakesh Christopher; Tangri, Navdeep; Duhamel, Todd Ashley
Abstract: Objective: The associations of moderate‐vigorous physical activity (MVPA) bouts and patterns of sedentary time (ST) with frailty according to cardiovascular disease (CVD) status are unknown. Methods: Accelerometry in adults ≥50 years old from the 2003‐2004 and 2005‐2006 National Health and Nutrition Examination Survey were used. Bouted and sporadic MVPA in ≥10‐minute or <1‐minute bouts were assessed based on meeting a percentage of physical activity guidelines of 150 minutes/wk, respectively. ST patterns included: prolonged ST lasting ≥30 minutes, and the frequency, intensity, and duration of breaks from ST. A 46‐item frailty index defined frailty . Multivariable linear regression was used. Results: There were 827 and 1490 CVD‐free and CVD participants, respectively. Meeting a higher percentage of the physical activity guidelines through bouted MVPA was associated with lower frailty in CVD‐only participants ( P < 0.05 for CVD interaction). Sporadic MVPA was associated with lower frailty levels in both groups. Prolonged ST was associated with worse frailty in CVD ( P > 0.05 for CVD interaction). Frequency of ST breaks was not associated with frailty. Average ST break intensity was protective in both groups. The duration of breaks in ST was associated with lower frailty in CVD participants only ( P > 0.05 for CVD interaction). Conclusion: Insufficient MVPA and prolonged ST are detrimental despite CVD status.